Work Readiness Reviewed From Proactive Personality and Psychological Capital - Alya, Adinda; Rasyid, Miranti; Suhesty, Aulia; Handayani, Nanik (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2024)
Several factors, including proactive personality and psychological capital, influence work readiness. This study examines the influence of proactive personality and psychological capital on work readiness with a quantitative approach. The subjects of the study are final-year students from the Faculty of Social and Political Sciences at Mulawarman University, consisting of cohorts from 2016-2021, selected using a random sampling technique. The data are collected through scales of work readiness, proactive personality, and psychological capital. The data analysis technique used is multiple linear regression. The collected data were analyzed using the Statistical Package for Social Science (S.P.S.S.) program version 26.0 for Windows. This study's results indicate a significant influence of proactive personality and psychological capital on work readiness, as shown by the major hypothesis results: F = 21.291, R² = 0.428, and p = 0.000. This study concludes that there is a significant influence between proactive personality and psychological capital on work readiness.